2013
DOI: 10.1111/chd.12135
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Annular Plane Systolic Excursion for the Assessment of Ventricular Function in Adults Operated on with Mustard Procedure for Complete Transposition of the Great Arteries

Abstract: Our results indicate that in these patients TAPSE is not a useful measure of RV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
0
17
1
Order By: Relevance
“…(55) Importantly, “normal” reproducible values for some of these metrics are emerging. (55–60) Volumetric 3D analysis of the RV overcomes geometric assumptions and is often reliable. (6163) Knowledge-based reconstruction of systemic RV from specific data based algorithms is a promising new technique but is user dependent and reliant upon adequate acoustic windows and sector size.…”
Section: Discussionmentioning
confidence: 99%
“…(55) Importantly, “normal” reproducible values for some of these metrics are emerging. (55–60) Volumetric 3D analysis of the RV overcomes geometric assumptions and is often reliable. (6163) Knowledge-based reconstruction of systemic RV from specific data based algorithms is a promising new technique but is user dependent and reliant upon adequate acoustic windows and sector size.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, patients with d-transposition of the great arteries and systemic RVs after atrial redirection procedures (Mustard/Senning operations) also demonstrate a predominance of circumferential strain over longitudinal strain on speckle-tracking echocardiography of the RV [1, 7, 8, 23]. Values of TAPSE are diminished in this population as well and correlate poorly with RVEF [4, 8]. …”
Section: Discussionmentioning
confidence: 99%
“…Among the standard echocardiographic indices of the systolic RV function, only fractional area change differed between the subgroups, and the nonparametric indices of the systolic RV function were similar in the overweight/obese and normal weight patients. However, these parameters are usually applied to evaluate the subpulmonary RV, and some investigators suggested that they are not suitable for systemic RV assessment [14,15].…”
Section: Discussionmentioning
confidence: 99%